NETRALITAS POLRI DALAM PESTA DEMOKRASI PEMILU PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN - Teguh Soedarsono (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
This article focuses on the policy of neutrality of Indonesian police in general election either in legislatives or executives election. Basically, the policy of neutrality is a form of human rights violation in terms of democracy state. Through the policy, rights to vote as well as to be voted for Indonesian police is neglected. As a result, there is a democracy impair and not in line with constitution. Using social analysis technique, this article provides a constitutional critique for returning the rights of the police in the context of civic education empowerment.